PENGARUH PELATIHAN HYGIENE DAN SANITASI TERHADAP PENGETAHUAN, SIKAP DAN TINDAKAN PENJAMAH MAKANAN DI INSTALASI GIZI RS H. AMRI TAMBUNAN DELI SERDANG - Rohani Retnauli Simanjuntak (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Food handler is a major factor of food poisoning because it directly touches food. The knowledge and attitude of food handler on hygiene and sanitation can affect the application of hygiene and sanitation in food maintenance process. Poor hygiene and sanitation in food maintenance can affect the quality of food produced. Efforts to improve food-enhancing skills to produce quality food, there is a need for food hygiene and sanitation training. The purpose of this study was to analyses the effect of hygiene and sanitation training on the knowledge, attitudes and action of food-processor. This is a quasi experiment study with pre and post test draft with 12 samples. Knowledge, attitudes and practices data were obtained through questionnaires. The results show that there was a significant improvement before and after the training (knowledge : 6.08±0.99 and 7.83±0.93) values P = 0,000, the sample attitude 18.08 ± 1.56 to 25.25 ± 1.42 values P = 0,000 and practices 9.67±2.30 to 15.75±1.35. Another results showed that there were affect of hygiene and sanitation training of knowledge (p = 0,000 < 0.05), attitude (p=0,000 < 0.05) and action (p = 0,000 < 0.05) food handler in the nutrition installation of Deli Serdang regional hospital.